Corrigendum to “Vent-specific unrest at Pavlof Volcano, Alaska: Insights from multidisciplinary data” [Journal Volcanology and Geothermal Research 468 (2025) 108465] - Darren Tan; David Fee; Pavel Izbekov; Taryn Lopez; Társilo Girona; Vanesa Burgos; Stephen McNutt; Matthew Haney; Valerie Wasser; Jessica Larsen; Ronni Grapenthin; Mario Angarita; et al. (Journal of Volcanology and Geothermal Research, 2026)

Vent-specific unrest at Pavlof Volcano, Alaska: Insights from multidisciplinary data - Darren Tan; David Fee; Pavel Izbekov; Taryn Lopez; Társilo Girona; Vanesa Burgos; Stephen McNutt; Matthew Haney; Valerie Wasser; Jessica Larsen; Ronni Grapenthin; Mario Angarita; et al. (Journal of Volcanology and Geothermal Research, 2025)

The acoustics of bulge rise and rupture at Strokkur geyser - Julia E. Gestrich; Corrado Cimarelli; David Fee; Antonio Capponi; Caron E. J. Vossen; Markus Schmid (Bulletin of Volcanology, 2025)
Geysers are natural geothermal features that episodically erupt hot water and steam due to the buildup and release of subsurface vapor bubbles. At Strokkur geyser, Iceland, eruptions begin with the growth of a surface bulge caused by rising bubble clusters, followed by gradual rupture and disintegration into a water fountain. In this study, we investigate the high-resolution acoustic and visual signatures of this initial phase of the eruption, providing detailed insights into the fluid dynamics that govern bulge formation and rupture. While similar eruptive behavior is sometimes observed in low-viscosity volcanic systems, Strokkur offers a uniquely transparent medium in which processes like bubble rise and clustering can be directly observed, providing analogies to otherwise obscured dynamics in lava or mud-dominated settings. We combine low-frequency infrasound and high-frequency audio recordings with high-speed video, using synchronized data to track the evolution of the bulge. The results demonstrate that infrasound effectively detects bulge growth, while the onset of rupture is marked by a rise in audio-frequency amplitude. A monopole model is used to simulate pressure variations during bulge growth. The observed decompression signal is associated with the downward water motion during bulge disintegration. These findings improve our understanding of geyser eruption dynamics and suggest how acoustic monitoring can provide valuable information about subsurface processes in both geysers and volcanoes, such as dome inflation or gas bubble accumulation beneath magma surfaces.

Identifying precursors and tracking pulses of magma ascent in multidisciplinary data during the 2018–2023 phreatomagmatic eruption at Semisopochnoi Island, Alaska - John J. Lyons; Darren Tan; Mario Angarita; Matthew W. Loewen; Taryn Lopez; Ronni Grapenthin; Alicia J. Hotovec-Ellis; David Fee; Matthew M. Haney (Journal of Volcanology and Geothermal Research, 2025)

Integrating plasmasphere, ionosphere and thermosphere observations and models into a standardised open access research environment: The PITHIA-NRF international project - Anna Belehaki; Ingemar Häggström; Tamas Kiss; Ivan Galkin; Anders Tjulin; Mária Miháliková; Carl-Fredrik Enell; Gabriel Pierantoni; Yin Chen; Gergely Sipos; Sean Bruinsma; Viviane Pierrard; et al. (Advances in Space Research, 2025)

From field station to forecast: managing data at the Alaska Volcano Observatory - Michelle L. Coombs; Cheryl E. Cameron; Hannah R. Dietterich; Eleanor S. Boyce; Aaron G. Wech; Ronni Grapenthin; Kristi L. Wallace; Tom Parker; Taryn Lopez; Scott Crass; David Fee; Matthew M. Haney; et al. (Bulletin of Volcanology, 2024)

Infrasound observations and constraints on the 2018 eruption of Kīlauea Volcano, Hawaii - Weston Thelen; Gregory Waite; John Lyons; David Fee (Bulletin of Volcanology, 2022)

Volcano infrasound: progress and future directions - Leighton M. Watson; Alexandra M. Iezzi; Liam Toney; Sean P. Maher; David Fee; Kathleen McKee; Hugo D. Ortiz; Robin S. Matoza; Julia E. Gestrich; Jordan W. Bishop; Alex J. C. Witsil; Jacob F. Anderson; et al. (Bulletin of Volcanology, 2022)
Over the past two decades (2000–2020), volcano infrasound (acoustic waves with frequencies less than 20 Hz propagating in the atmosphere) has evolved from an area of academic research to a useful monitoring tool. As a result, infrasound is routinely used by volcano observatories around the world to detect, locate, and characterize volcanic activity. It is particularly useful in confirming subaerial activity and monitoring remote eruptions, and it has shown promise in forecasting paroxysmal activity at open-vent systems. Fundamental research on volcano infrasound is providing substantial new insights on eruption dynamics and volcanic processes and will continue to do so over the next decade. The increased availability of infrasound sensors will expand observations of varied eruption styles, and the associated increase in data volume will make machine learning workflows more feasible. More sophisticated modeling will be applied to examine infrasound source and propagation effects from local to global distances, leading to improved infrasound-derived estimates of eruption properties. Future work will use infrasound to detect, locate, and characterize moving flows, such as pyroclastic density currents, lahars, rockfalls, lava flows, and avalanches. Infrasound observations will be further integrated with other data streams, such as seismic, ground- and satellite-based thermal and visual imagery, geodetic, lightning, and gas data. The volcano infrasound community should continue efforts to make data and codes accessible and to improve diversity, equity, and inclusion in the field. In summary, the next decade of volcano infrasound research will continue to advance our understanding of complex volcano processes through increased data availability, sensor technologies, enhanced modeling capabilities, and novel data analysis methods that will improve hazard detection and mitigation.

Evidence for near-source nonlinear propagation of volcano infrasound from Strombolian explosions at Yasur Volcano, Vanuatu - Sean P. Maher; Robin S. Matoza; Arthur Jolly; Catherine de Groot-Hedlin; Kent L. Gee; David Fee; Alexandra M. Iezzi (Bulletin of Volcanology, 2022)
Volcanic eruption source parameters may be estimated from acoustic pressure recordings dominant at infrasonic frequencies (< 20 Hz), yet uncertainties may be high due in part to poorly understood propagation dynamics. Linear acoustic propagation of volcano infrasound is commonly assumed, but nonlinear processes such as wave steepening may distort waveforms and obscure the sourcing process in recorded waveforms. Here we use a previously developed frequency-domain nonlinearity indicator to quantify spectral changes due to nonlinear propagation primarily in 80 signals from explosions at Yasur Volcano, Vanuatu. We find evidence for $$\le$$ ≤ 10 −3 dB/m spectral energy transfer in the band 3–9 Hz for signals with amplitude on the order of several hundred Pa at 200–400 m range. The clarity of the nonlinear spectral signature increases with waveform amplitude, suggesting stronger nonlinear changes for greater source pressures. We observe similar results in application to synthetics generated through finite-difference wavefield simulations of nonlinear propagation, although limitations of the model complicate direct comparison to the observations. Our results provide quantitative evidence for nonlinear propagation that confirms previous interpretations made on the basis of qualitative observations of asymmetric waveforms.

High-speed lava flow infrasound from Kīlauea’s fissure 8 and its utility in monitoring effusion rate - John J. Lyons; Hannah R. Dietterich; Matthew P. Patrick; David Fee (Bulletin of Volcanology, 2021)

Evolving infrasound detections from Bogoslof volcano, Alaska: insights from atmospheric propagation modeling - Hans F. Schwaiger; John J. Lyons; Alexandra M. Iezzi; David Fee; Matthew M. Haney (Bulletin of Volcanology, 2020)

Did ice-charging generate volcanic lightning during the 2016–2017 eruption of Bogoslof volcano, Alaska? - Alexa R. Van Eaton; David J. Schneider; Cassandra M. Smith; Matthew M. Haney; John J. Lyons; Ryan Said; David Fee; Robert H. Holzworth; Larry G. Mastin (Bulletin of Volcanology, 2020)

Infrasound generated by the 2016–2017 shallow submarine eruption of Bogoslof volcano, Alaska - John J. Lyons; Alexandra M. Iezzi; David Fee; Hans F. Schwaiger; Aaron G. Wech; Matthew M. Haney (Bulletin of Volcanology, 2020)

Co-eruptive tremor from Bogoslof volcano: seismic wavefield composition at regional distances - Matthew M. Haney; David Fee; Kathleen F. McKee; John J. Lyons; Robin S. Matoza; Aaron G. Wech; Gabrielle Tepp; Cheryl Searcy; T. Dylan Mikesell (Bulletin of Volcanology, 2020)

Constraints on eruption processes and event masses for the 2016–2017 eruption of Bogoslof volcano, Alaska, through evaluation of IASI satellite SO2 masses and complementary datasets - Taryn Lopez; Lieven Clarisse; Hans Schwaiger; Alexa Van Eaton; Matthew Loewen; David Fee; John Lyons; Kristi Wallace; Cheryl Searcy; Aaron Wech; Matthew Haney; David Schneider; et al. (Bulletin of Volcanology, 2020)

Characteristics of thunder and electromagnetic pulses from volcanic lightning at Bogoslof volcano, Alaska - Matthew M. Haney; Alexa R. Van Eaton; John J. Lyons; Rebecca L. Kramer; David Fee; Alexandra M. Iezzi; Robert P. Dziak; Jacob Anderson; Jeffrey B. Johnson; Jeff L. Lapierre; Michael Stock (Bulletin of Volcanology, 2020)

Seismo-acoustic evidence for vent drying during shallow submarine eruptions at Bogoslof volcano, Alaska - David Fee; John Lyons; Matthew Haney; Aaron Wech; Christopher Waythomas; Angela K. Diefenbach; Taryn Lopez; Alexa Van Eaton; David Schneider (Bulletin of Volcanology, 2020)
Characterizing the state of the volcanic vent is key for interpreting observational datasets and accurately assessing volcanic hazards. This is particularly true for remote, complex eruptions such as the 2016–2017 Bogoslof volcano, Alaska eruption sequence. Bogoslof’s eruptions in this period were either shallow submarine or subaerial, or some combination of both. Our results demonstrate how low-frequency sound waves (infrasound), integrated with seismic and satellite data, can provide unique insight into shallow vent processes, otherwise not available. We use simple metrics, such as the infrasound frequency index (FI), event duration, and acoustic-seismic amplitude ratio, to look at changes in the elastic energy radiation and infer changes in seawater access to the vent. Satellite imagery before and after selected eruptions is used to ground-truth inferences on vent conditions. High FI and gradual increases in infrasound frequency content at Bogoslof correspond with transitions from submarine to subaerial vent conditions and a diminished or absent role of water, likely resulting in a drying out of the vent region. Event durations generally correlate with high FI and the range of FI values for each event, suggesting long duration events were more effective at drying out the vent region. A trend from low to high acoustic-seismic amplitude ratios for some long duration events also suggests an increase in acoustic efficiency as the vent dried out. We demonstrate that infrasound can serve as a robust indicator of seawater involvement for Bogoslof and other shallow submarine eruptions that may not be inferable from other datasets, particularly in near-real-time.

The 2016–2017 eruption of Bogoslof volcano, Alaska: preface to the special issue - Christopher F. Waythomas; John J. Lyons; David Fee; Kristi L. Wallace (Bulletin of Volcanology, 2019)

First recorded eruption of Nabro volcano, Eritrea, 2011 - Berhe Goitom; Clive Oppenheimer; James O. S. Hammond; Raphaël Grandin; Talfan Barnie; Amy Donovan; Ghebrebrhan Ogubazghi; Ermias Yohannes; Goitom Kibrom; J- Michael Kendall; Simon A. Carn; David Fee; et al. (Bulletin of Volcanology, 2015)

The 2013 eruption of Pavlof Volcano, Alaska: a spatter eruption at an ice- and snow-clad volcano - Christopher F. Waythomas; Matthew M. Haney; David Fee; David J. Schneider; Aaron Wech (Bulletin of Volcanology, 2014)

Shallow degassing events as a trigger for very-long-period seismicity at Kīlauea Volcano, Hawai‘i - Matthew Patrick; David Wilson; David Fee; Tim Orr; Don Swanson (Bulletin of Volcanology, 2011)

The circumsphere as a tool to assess distortion in [4Fe-4S] atom clusters - James A. Fee; Jesus M. Castagnetto; David A. Case; Louis Noodleman; C. David Stout; Rhonda A. Torres (JBIC Journal of Biological Inorganic Chemistry, 2003)